Diffuse reflectance spectroscopy for optical nerve identification - Preliminary ex vivo results for feedback controlled oral and maxillofacial laser surgery - Stelzle, Florian; Zam, Azhar; Adler, Werner; Douplik, Alexandre; Tangermann-Gerk, Katja; Nkenke, Emeka; Neukam, Friedrich Wilhelm; Schmidt, Michael (Physics Procedia, 2010)
Objective: Laser surgery has many advantages. However, due to a lack of haptic feedback it is accompanied by the risk of iatrogenic nerve damage. The aim of this study was to evaluate the possibilities of optical nerve identification by diffuse reflectance spectroscopy to set the base for a feedback control system to enhance nerve preservation in oral and maxillofacial laser surgery. Materials and Methods: Diffuse reflectance spectra of nerve tissue, skin, mucosa, fat tissue, muscle, cartilage and bone (15120 spectra) of ex vivo pig heads were acquired in the wavelength range of 350-650 nm. Tissue differentiation was performed by principal components analysis (PCA) followed by linear discriminant analysis (LDA). Specificity and sensitivity were calculated by receiver operating characteristic (ROC) analysis and the area under curve (AUC). Results: Nerve tissue could correctly be identified and differed from skin, mucosa, fat tissue, muscle, cartilage and bone in more than 90% of the cases (AUC results) with a specificity of over 78% and a sensitivity of more than 86%. Conclusion: Nerve tissue can be identified by diffuse reflectance spectroscopy with high precision and reliability. The results may set the base for a feedback system to prevent iatrogenic nerve damage performing oral and maxillofacial laser surgery. © 2010 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Laser surgery; Nerve preservation; Optical tissue differentiation; Oral and maxillofacial surgery; Remote surgical methods